A further electrochemical investigation on solutions to high energetical power sources: isomerous compound 0.75Li1.2Ni0.2Mn0.6O2·0.25LiNi0.5Mn1.5O41. Issue 47 (27th May 2015) - Zheng, Zhuo; Wu, Zhen-Guo; Zhong, Yan-Jun; Shen, Chong-Heng; Hua, Wei-Bo; Xu, Bin-Bin; Yu, Chong; Zhong, Ben-He; Guo, Xiao-Dong
<x xml:space="preserve">Abstract</x> A 0.75Li1.2Ni0.2Mn0.6O2·0.25LiNi0.5Mn1.5O4 cathode material with outstanding electrochemical properties has been synthesized by introducing spinel LiNi0.5Mn1.5O4 material to fill the surface gaps in pristine lithium-rich layered Li1.2Ni0.2Mn0.6O2 in a molar ratio of 25 : 75.